Language Attitude of Millennial Sundanese Speakers: A Sociolinguistic Perspective - Trianto, Ikmal; Muniroh, R. Dian Dia-an; Gunawan, Wawan; Isnendes, Retty; Wirza, Yanty (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study aims to identify the language attitude tendencies of the millennial Sundanese-speaking group in the city of Bandung, along with the factors that influence them. A sociolinguistic approach using a mixed-methods design is employed to measure the dominance of language attitudes among millennials within various domains of their daily communication. This can indicate whether this generation is inclined to maintain their mother tongue or shift toward using other languages in their interactions. A total of 97 individuals responded to the distributed questionnaire; however, only 80 met the predetermined criteria. In this context, the researcher utilized a modified version of the instrument developed by Cohn (2013). In addition, interviews and observations were conducted to gain a deeper perspective on the language attitude tendencies of this millennial group. Millennials like Indonesian and international languages better than Sundanese online because they perceive them as more functional and global. However, though Sundanese use declines in everyday life, a significant majority of respondents are also concerned about language conservation and have encouraged electronic means of preserving Sundanese to thrive in new communication spaces. This study determines that while millennials are cognizant of Sundanese’s cultural and identity value, pragmatic limitations such as speech-level complexity and technological influence are contributing factors in its gradual decline. The findings emphasize the need for innovative strategies, including online content creation and policy implementation, to preserve the use and liveliness of Sundanese among the younger generations.